Pola-pola hubungan sosial dan pendapatan tukang becak di Ujungpandang - Latief, Muh. Iqbal (Lembaga Penelitian, Universitas Hasanuddin, 1991)
Income of tricycle pullers in relation with the socioeconomic and demography in Ujungpandang, Sulawesi Selatan Province; research report.